ANALISIS KURVA SURVIVAL KAPLAN MEIER MENGGUNAKAN UJI LOG RANK (Studi Kasus :Pasien Penyakit Jantung Koroner di RSUD Undata Palu) - Arianti Suhartini; Rita Rahmawati; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2018)
Coronary heart disease is one of the leading causes of death in the world, including Indonesia. Based on doctor-diagnosed interviews, coronary heart disease’s prevalence in Indonesia on 2013 is 0,5% and based on a doctor-diagnosed is 1,5%. Central Sulawesi is ranked first and second for prevalence based on doctor-diagnosed interviews and doctor-diagnosed. The high number of people with coronary heart disease caused by lack of self-awareness in lifestyle changes. One of the parameters used to assess the success of treatment is the probability of survival. Survival analysis is a data analysis where the outcome of the variables studied is the time until an event occurs. This study raised the problem of survival of coronary heart patients at Undata Palu Hospital which is the main referral hospital for Central Sulawesi region. This research uses nonparametric method that is Kaplan Meier and Log Rank Test based on six factors are age, gender, stadium, disease status, complication and status of anemia. Nonparametric methods do not follow a particular distribution for survival time. Kaplan Meier's survival curve will describe the patient's characteristics of survival probability and followed by a Log Rank test to see if there are differences between curves. The result of analysis and discussion based on Log Rank test result showed that the factors of age, sex and disease status differ significantly. Keywords: Coronary heart disease, RSUD Undata Palu, Kaplan Meier analysis, Log Rank test.